Updated Geochemical Characterization of Hydrocarbon Potential of Surface Sample in Lariang-Karama Sub-Basin, West Sulawesi, Indonesia - Yarra Sutadiwiria; Muhammad Taufiq Fathaddin; Imam Setiaji Ronoatmojo; Dewi Syavitri; Cahyaningratri P R; Barona Belladesta; Yeftamikha Yeftamikha; Andy Livsey (Scientific Contributions Oil and Gas, 2024)
The Lariang-Karama Sub-Basin is situated within the Makassar Basin, located in the West Sulawesi region. It has source of rocks which has the potential to produce hydrocarbons and to become a target for new field discoveries in hydrocarbon exploration activities. It is on this basis that the authors are interested in conducting research in the Makassar Basin area and its surroundings, which has been carried out since 2017. This is a comprehensive literature review study from 2017 to 2022, focusing on the origin and composition of biomarkers, paleogeography of facies sources from oil seeps (2017-2018), paleofacies and biomarker characteristics of Paleogene to Neogene rocks (2019), contribution of terrestrial materials based on geochemical and biostratigraphic analysis (2020), tectonic processes occurring in the basin, and geochemical characterization of source rocks in the research area (2022). The FS-12 surface sample in shale may belong to the Kalumpang Formation, located in West Sulawesi. The results of TOC analysis were 0.62%, indicating sufficient quantity. Based on the results of the cross plot between HI values of < 50 and Tmax of 499 Â°C, the category was found to be overmature and could not produce hydrocarbons. The results of this research, along with those of previous research and the latest geochemical study, were obtained in the West Sulawesi region and the eastern Makassar Strait. These findings consisted of marine shale source rocks in West Sulawesi and lacustrine shale source rocks in the eastern Makassar Strait